DNA methylation at birth within the promoter of ANRIL predicts markers of cardiovascular risk at 9 years. Issue 1 (December 2016) - Murray, Robert; Bryant, Jennifer; Titcombe, Phil; Barton, Sheila; Inskip, Hazel; Harvey, Nicholas; Cooper, Cyrus; Lillycrop, Karen; Hanson, Mark; Godfrey, Keith
Abstract Aims Antisense non-coding RNA in the INK4 locus (ANRIL) fixed genetic variants have consistently been linked with coronary heart disease (CHD) risk. We investigated relationships between perinatal ANRIL promoter DNA methylation and CHD risk markers in children aged 9 years. Genetic variants in the non-coding RNA ANRIL identify it as an important CHD risk locus. Increasing evidence suggests that the early life environment may act through epigenetic processes to influence later CHD risk markers such as increased arterial pulse wave velocity (PWV, a measure of arterial stiffness) blood pressure or heart rate. Methods and results Using pyrosequencing, ANRIL DNA methylation at nine CpG sites was measured in the umbilical cord from 144 children in a UK mother-offspring cohort and related to the descending aorta PWV measured by velocity-encoded phase contrast MRI at age 9 years. Perinatal methylation was not associated with child's later blood pressure, but higher methylation at CpG5 was associated with increased childhood PWV (β  = 0.066 m/s/10 % methylation increase [95 % CI, 0.004 to 0.128], p  = 0.037); 10 % decreases in methylation at CpG1 and CpG2 were associated with increased heart rate (CpG1β  = 1.93 [0.07 to 3.8] beats/min, p  = 0.041; CpG2β  = 2.30 [0.18 to 4.41] beats/min, p  = 0.033, accounting for potential confounding variables). The associations with perinatal ANRIL promoter methylation were independent of neighbouring fixed genetic variants. Conclusions Our findings suggest developmental epigenetic regulation of ANRIL promoter methylation as a factor in later CHD risk in children.